Utilização da técnica CF-LIBS para análises espectroscópicas em ligas metálicas - Carneiro, Deborah Deah Assis (2019)
The Laser Induced Breakdown Spectroscopy (LIBS) technique is based on the analysis of the laser-generated plasma light spectrum. It can be used to identify chemical elements as well as to quantify them. The aim of this work is to use the CF-LIBS technique to quantify metal samples in atomic mass and volume seeking the best way to obtain good results, such as the insertion of argon in the experiment and the analysis of the self absorption of the lines. Were analyzed laboratory manipulated tin and lead alloys with different concentrations and a certified sample of copper, chromium, nickel and silicon (BM-180). The lead and tin samples contained concentrations ranging from 15% to 85% in a total of five samples. Experiments were performed using the LIBS experimental apparatus on all samples to obtain the line spectra. From this, temperature, density and concentration calculations were made based on the Saha-Boltzmann and CF-LIBS equations. In addition, the self-absorption criteria of the lines were observed and the lines that were self-absorbed were corrected so as not to interfere in the final result. As a result, very close numbers were obtained from the actual sample values. In the samples of Sn and Pb the greatest uncertainties found were 13.435% atomic mass and 12.111% by volume in the sample containing 85% Sn and 15% Pb, both values in the Pb element. BM-180, the largest uncertainty was in volume, at 29.648% in element Cr. The results obtained were satisfactory, since the results were very close to reality, proving that CF-LIBS can be an excellent tool for calculating concentrations.